How does digital literacy affect the health status of senior citizens? Micro-level evidence from the CFPS data - Xiaoyi Chen; Nian Wang (BMC Health Services Research)
Abstract Background The popularization of the Internet and digital technology has called for higher digital literacy among citizens, especially the elderly. However, most existing studies didn’t measure digital literacy at the micro level, and the impact mechanism has rarely been discussed. The purpose of this study is to clarify whether and how digital literacy affects the health status of senior citizens. Methods The data used in this study are collected from the China Family Panel Studies (CFPS) from three periods: 2016, 2018, and 2020. The balanced panel data comprised 7836 samples, with 2612 samples per year. Based on the CFPS data, this study constructs a balanced panel and employs a two-way fixed-effects model for the estimation. The instrumental variable (IV) method is employed for tackling the endogenous problems. Next, the mediation effect model is applied to identify the influencing mechanism. Results First, digital literacy can improve the health status of senior citizens. This result remains valid after introducing lagged explanatory variables and addressing the endogeneity issues. Second, social support acts as a partial mediator in the relationship between digital literacy and the health status of senior citizens. Third, the heterogeneity analysis reveals that the effect of digital literacy on the health status of senior citizens varies across age groups, urban–rural types, and education levels. Conclusions This study examines the impact of digital literacy on the health status of senior citizens at the micro-level and identifies the mediation mechanism. The results enhance our understanding of the positive effects of digitalization on aging society and offer useful insights for the government in formulating more targeted active aging strategies.